Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae) - Morffe, Jans; García, Nayla; Breugelmans, Karin; Adams, Byron J. (Zootaxa, 2018)
The status of Longior alius García & Coy, 1994 (Nematoda: Thelastomatoidea: Hystrignathidae) is discussed on the basis of new material obtained from its type host Antillanax pertyi (Kaup, 1869) (Coleoptera: Passalidae) from Limonar, Guantánamo province, Cuba, near the type locality. Based on morphological and molecular studies L. alius is considered synonymous with L. longior Morffe & García, 2011. L. longior and L. similis Morffe, García & Ventosa, 2009 are redescribed and illustrated with the aid of SEM. New locality records for both species are given. The conspecificity of females and males of both species is supported by comparison of the D2-D3 segment of the 28S LSU rDNA. The inter-specific differences and phylogenetic position of L. longior and L. similis are discussed.